Motivasi Bertani Pada Masyarakat Gayo di Kampung Cemparam Lama Kecamatan Mesidah Kabupaten Bener Meriah - Hermawansyah Hermawansyah; Nirzalin Nirzalin; Alwi Alwi (Jurnal Community, 2022)
This article aims to provide a descriptive description of the series of motivations for the actions of the Gayo community in the Cemparam Lama village, Mesidah sub-district, Bener Meriah Regency in carrying out cayenne pepper farming which is intercropped with existing coffee plants. This study uses qualitative methods, data obtained by observation, interviews and relevant documents. The research informants consisted of several farmers who carried out this agricultural pattern, coffee toke who were involved in purchasing coffee plantation products and palawija toke who were actively involved in buying cayenne pepper. This study found that the community's actions in intercropping agriculture varied widely as motivated by several motivations including the existence of traditional patterns that had been passed down from generation to generation, the existence of motivation based on the sintamental nature or the nature of competition among the community, and motivated by the encouragement of religious values which became the foundation. in doing business and which is most strongly influenced by the desire to increase income which is used to support the existing lifestyle. So that this study finds one knowledge, namely although instrumental rationality is dominant, traditional rationality cannot be completely abandoned, in fact instrumental rationality and traditional rationality are used varally by Gayo farmers.